2016
DOI: 10.2147/copd.s113978
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin modulates the effect of histone modification on the expression of chemokines by type II alveolar epithelial cells in a rat COPD model

Abstract: BackgroundStudies have suggested that histone modification has a positive impact on various aspects associated with the progression of COPD. Histone deacetylase 2 (HDAC2) suppresses proinflammatory gene expression through deacetylation of core histones.ObjectiveTo investigate the effect of histone modification on the expression of chemokines in type II alveolar epithelial cells (AEC II) in a rat COPD model and regulation of HDAC2 expression by curcumin in comparison with corticosteroid.Materials and methodsThe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…On the other hand, in MCF7 BC cell line Cur-SLN causes the deregulation of molecules belonging to apoptosis induction, inflammation signaling (sustained by cytokine and platelet activation pathways), tyrosine metabolism known to be involved in cellular stress response and in glucagon signaling pathway, recently described as modulated by curcumin to improve glucose tolerance (Table 4) 3237 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, in MCF7 BC cell line Cur-SLN causes the deregulation of molecules belonging to apoptosis induction, inflammation signaling (sustained by cytokine and platelet activation pathways), tyrosine metabolism known to be involved in cellular stress response and in glucagon signaling pathway, recently described as modulated by curcumin to improve glucose tolerance (Table 4) 3237 .…”
Section: Resultsmentioning
confidence: 99%
“…In this context, the phosphatidylinositol-3-kinase (PI3K)/protein kinase B (AKT) pathway, usually activated in onset and neoplastic development, is inhibited by curcumin. This process could constitute a key molecular target for anti-cancer therapies as it represents a negative regulator of tumor progression processes and metastasis 32,41,42 .…”
Section: Discussionmentioning
confidence: 99%
“…Specifically in COPD, curcumin has been shown in animal models to have a beneficial effect in smooth muscle cells and improve the mean pulmonary artery pressure and right ventricular myocardial infarction (RVMI) through stimulating the suppressor of cytokine signalling (SOCS) -3/JAK2/STAT signalling pathways [ 193 ]. In another model, curcumin was shown to suppress chemokines and affect corticosteroid sensitivity in COPD through modulating Histone deacetylase 2 (HDAC2) expression and its effect on histone modification [ 194 ]. Another animal model showed that curcumin attenuates alveolar epithelial injury in COPD, which may be partially due to the down-regulation of Protein 66 homologous- collagen homologue (p66Shc) [ 195 ].…”
Section: Methodsmentioning
confidence: 99%
“…Curcumin can significantly decrease the number of neutrophils and macrophages in the BAL fluid, and reduce the apoptosis index of alveolar epithelial cells to attenuate alveolar epithelial damage in COPD, and may be associated with down-regulating the expression of p66Shc ( Zhang et al, 2016 ). Curcumin can also suppress chemokine expression by restoring HDAC2 expression and function on histone modification to attenuate COPD development ( Gan et al, 2016 ). Also, curcumin effectively reduced CS-induced inflammation responses and improved pulmonary function, presumably by up-regulating peroxisome proliferators-activated receptor γ (PPARγ) and inhibiting NF-κB activation ( Li et al, 2019 ).…”
Section: Prevention and Present Treatmentmentioning
confidence: 99%